VEGETABLE PEA BREEDING ON TECHNOLOGY - I. P. Kotlyar; V. A. Ushakov; I. M. Kaygorodova; E. P. Pronina (Овощи России, 2019)
Breeding of high-tech varieties of vegetable peas is a priority ефыл selection at the present stage. The main requirement of processing enterprises is full and timely loading of production lines with high-quality raw materials. Peas should be aligned in size, of intense green color with high biochemical parameters. Therefore, the newly created varieties should combine a number of characteristics: high and stable yields, simultaneous ripening, resistance of the stem to lodging, resistance to most common diseases. The combination of these features allows to realize the potential of the culture fully, and to find wide application in production for created varieties. Since the 80s of the last century, FSBSI «FSVC» (Moscow region) has been actively working to increase the suitability of vegetable pea varieties for mechanized harvesting. Since these years, a number of varieties with strong shortened internodes and stem height not more than 80-90 cm have been created. Reducing plant height has improved the manufacturability of vegetable pea varieties, the stems resistance to lodging during the technical stage of ripeness has been significantly increased. However, in the biological stage of ripeness, the stem degree of lodging has been preserved, which creates additional difficulties in the seed production of vegetable peas. Since 2008, the direction of breeding has been adjusted to improve the stems resistance to lodging in combination with other economically significant traits (determinant type of growth, mustache type of leaf, green color of peas, duration of the technical stage of ripeness). As a result of this work, new varieties Cruiser, Viking, Triumph, Corsair, Barin, Hercules, Egorka have been created. The work is to introduce these varieties into production is being carried.